2004
DOI: 10.1007/s10557-005-5058-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effects of Rapid Bolus Administration of Aqueous Amiodarone Versus 10-Minute Cordarone I.V. Infusion on Mean Arterial Blood Pressure in Conscious Dogs

Abstract: Amio-Aqueous had significantly better hemodynamic profile permitting rapid intravenous administration. This is a significant advantage over the standard formulation, because Cordarone cannot be administered by rapid bolus due to excipient-related hypotension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…The results from the present study confirm the previously reported hypotensive liability of the conventional formulation of intravenous amiodarone 7,9,11–16 and extend the observation of hypotension to the maintenance infusion period. Moreover, these data indicate that administration of the maintenance dose alone, without having administered the loading dose, can produce significant hypotension.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The results from the present study confirm the previously reported hypotensive liability of the conventional formulation of intravenous amiodarone 7,9,11–16 and extend the observation of hypotension to the maintenance infusion period. Moreover, these data indicate that administration of the maintenance dose alone, without having administered the loading dose, can produce significant hypotension.…”
Section: Discussionsupporting
confidence: 91%
“…Presumably, this response is due to the cosolvents (i.e. polysorbate 80 and benzyl alcohol) used to formulate intravenous amiodarone 7,15 . In contrast with the conventional formulation of intravenous amiodarone, a formulation of amiodarone devoid of the cosolvents (i.e.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…Aqueous preparations of amiodarone (Amio-Aqueous d ) prevent hypotension in dogs and humans, and may be better suited for IV use. 9,10 Amiodarone and other class-III antiarrhythmics are associated with prolongation of the QT-interval and potential for proarrhythmia, specifically torsades de pointes. This complication is unlikely when amiodarone is used as a short-term IV infusion, 11 and we did not detect any significant QT-prolongation in the cases reported here.…”
mentioning
confidence: 99%